Bailyn, The Ideological Origins Of The American Revolution - Geib, George (Teaching History: A Journal of Methods, 1993)
Bernard Bailyn redirected much of the scholarship of the era of the American Revolution when he published the first edition of this volume in 1967. His study of the vast pamphlet literature of the era offered a fresh and exciting reinterpretation of political thought and theory from the 1760’s through the 1780’s. Bailyn rediscovered a debate over the sources and uses of power that had meaning in its own right, contributing centrally to the presentation and resolution of many economic, military, diplomatic, and constitutional questions.